A Study on Effect of Varying Levels of Oestrogen and Progesterone across Various Phases of Menstrual Cycle on Auditory and Visual Reaction Time among Young Women - Veena, C. N.; Vastrad, B. C.; Nandan, T. M. (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Women's reproductive system undergo cyclic modifications that might be viewed as teleological preparation of the female genital tract for fertilization and pregnancy. These cyclical fluctuations are also linked to cyclically changing ovarian steroid levels. Estrogen is thought to have extensive impacts across the brain regions involved in emotional and cognitive states. This study aimed to observe the effects of gonadal hormones on auditory and visual reaction time across various phases of menstrual cycle. The study was carried out on 30 healthy female volunteers having regular menstrual cycle belonging to the age group of 17-20 years studying in the first year MBBS at a tertiary care Institute using pitch change 1000 Hz reaction timer. The auditory and visual reaction times were found to be longer during the mid-proliferative phase compared to the premenstrual and mid-secretary phases in this investigation. The varying amounts of ovarian hormones over the regular monthly cycle affect auditory and visual reaction time, and this fact should be taken into account when evaluating women's neurological and behavioural abilities.